Critical experiences with sport and wellness technology digital coach – differences between young adults and young elderly - Kettunen, Eeva; Kari, Tuomas; Critchley, Will; Frank, Lauri (Taylor & Francis, 2023)
Both young adults and young elderly people have been found to be at a high risk of disengagement with physical activity. This makes both groups important targets for health and exercise promotion. Since sport and wellness technology has become popular among regular exercisers, it is worth studying how personal wellness devices could help both target groups in becoming more physically active. This study explores critical experiences during the implementation phase of a sport and wellness technology digital coach among young adults and young elderly. This qualitative study is based on a thematic analysis of 60 participants’ interviews conducted with the critical incident technique. The study reveals the experiences the users consider crucial during the initial phases of usage of sport and wellness technology digital coaching devices. The results show that positive critical incidents among young adults and young elderly are similar when learning about personal health and exercising. However, the role of supportive communication seems to be more important with the young elderly people. Functionality and usability issues play a big role in negative critical incidents. The findings highlight the importance of these critical experiences to the overall usage experience and their influence on users’ motivation to improve their fitness.
Keywords: coaching; digital technology; digital well-being; Digital coaching; sport and wellness technology; CIT; critical experiences; young adults; young elderly